STUDI KOMPARATIF KINERJA REKSADANA SAHAM SYARIAH DAN KONVENSIONAL STUDI KASUS DI INDONESIA - Ahmad Rifa’i; Muhammad Rafi Siregar (Institut Bisnis Muhammadiyah Bekasi, 2022)
This study aims to determine whether there is a difference between the performance of conventional and sharia mutual funds and to find out the difference between the sharia index (JII) and the conventional index (IHSG). The population of this research is all stock mutual funds that cooperate with Indo Premier Sekuritas. Based on the purposive sampling method, there were 65 samples consisting of 14 Islamic stock mutual funds and 51 conventional stock mutual funds. Empirical results show that the performance of Islamic mutual funds is lower than that of conventional mutual funds. In addition, the performance of Islamic and conventional equity mutual funds is better than JII and JCI.